2014
DOI: 10.1200/jco.2013.53.2820
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oophorectomy on Cancer Incidence and Mortality in Women With a BRCA1 or BRCA2 Mutation

Abstract: Purpose The purposes of this study were to estimate the reduction in risk of ovarian, fallopian tube, or peritoneal cancer in women with a BRCA1 or BRCA2 mutation after oophorectomy, by age of oophorectomy; to estimate the impact of prophylactic oophorectomy on all-cause mortality; and to estimate 5-year survival associated with clinically detected ovarian, occult, and peritoneal cancers diagnosed in the cohort. Patients and Methods Women with a BRCA1 or BRCA2 mutation were identified from an international reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
420
2
25

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 571 publications
(459 citation statements)
references
References 18 publications
12
420
2
25
Order By: Relevance
“…This led to the recommendation that BRCA1 mutation carriers should undergo RRSO by the age of 35 years. Finch et al (17) also observed that the rate of diagnosis of ovarian cancer was 4.0% if a BRCA1 mutation carrier chose to delay RRSO until the age of 40 years and that this rate increased to 14.2% with a delay until the age of 50 years.…”
Section: Indications For Rrsmentioning
confidence: 97%
See 3 more Smart Citations
“…This led to the recommendation that BRCA1 mutation carriers should undergo RRSO by the age of 35 years. Finch et al (17) also observed that the rate of diagnosis of ovarian cancer was 4.0% if a BRCA1 mutation carrier chose to delay RRSO until the age of 40 years and that this rate increased to 14.2% with a delay until the age of 50 years.…”
Section: Indications For Rrsmentioning
confidence: 97%
“…King et al (16) observed that the risk of developing ovarian and breast cancer at the age of 40, 50 and 60 years was 3, 21 and 40%, respectively, in BRCA1 mutation carriers and 2, 2 and 6%, respectively, in BRCA2 mutation carriers; they also reported that the risk of developing breast cancer at these ages was 21, 39 and 58%, respectively, in BRCA1 mutation carriers and 17, 34 and 48%, respectively, in BRCA2 mutation carriers. Finch et al (17) reported that the prevalence of occult carcinoma was 1.5% for BRCA1 mutation carriers who underwent oophorectomy at <40 years of age and 3.8%…”
Section: Indications For Rrsmentioning
confidence: 99%
See 2 more Smart Citations
“…This risk decreases considerably after prophylactic salpingo-oophorectomy and has substantial mortality benefits in BRCA1/2 mutation carriers. 8 In light of these considerations the ACA section 2713 may benefit from expanded provisions for genetic testing as a preventive service for individuals with a previous diagnosis of cancer.…”
Section: Commentarymentioning
confidence: 99%